Influence of maleic anhydride grafting on the positive temperature coefficient effect of semi‐conductive composites and space charge injection to XLPE insulation - Chengcheng Zhang; Sen Wang; Hong Zhao; Minghua Chen; Xuan Wang; Xiaohong Chi (High Voltage)
Abstract To suppress the resistivity positive temperature coefficient (PTC) effect of ethylene‐butyl acrylate copolymer (EBA)‐based semi‐conductive shielding layer and the injection of charge carriers to insulation layer, the polar molecule maleic anhydride (MAH) is grafted onto EBA macromolecules by melt blending and thermal grafting. The resistivity temperature stability of the grafted semi‐conductive composites, as well as the space charge distribution and direct current (DC) breakdown characteristics of cross‐linked polyethylene (XLPE) insulation using the composites as the electrode is investigated. The results show that MAH grafting can significantly reduce the volume resistivity of semi‐conductive composites, especially at a higher temperature, to suppress the PTC effect. And, the grafted semi‐conductive composites can prevent the injection of charge carriers to XLPE insulation from the semi‐conductive electrode to improve the space charge distribution and DC breakdown strength of XLPE insulation. The polar anhydride groups in the grafted MAH can enhance the interaction between EBA macromolecular chains and between EBA macromolecular chains and carbon black (CB) to improve the dispersion of CB in EBA matrix and the stability of the internal conductive network at the high temperature, improving the properties of EBA‐based semi‐conductive shielding layer and DC electrical properties of XLPE insulation layer.